Biofeedback Effect of Thoracic Excursion in Chest Expansion Training - Takeshi ANDO; Kazuya KAWAMURA; Junko FUJITANI; Tomokazu KOIKE; Yukiko NISHIGAKI; Hiroko MIZUGUCHI; Masashi FUJIMOTO; Masakatsu G. FUJIE (Journal of Biomechanical Science and Engineering, 2012)
Improvement of thoracic mobility is important for patients with diseases such as chronic obstructive pulmonary disease (COPD). Chest expansion training is often conducted to increase the thoracic excursion. However, it is difficult for the patients to keep the motivation for rehabilitation, because the chest excursion is only measured. In this paper, we analyze the effect of real-time biofeedback on thoracic excursion. In 30 healthy subjects, thoracic excursion was increased by 6 mm (17%) when using the biofeedback system. Our results confirmed that we have developed an effective system for rehabilitation of respiratory function.